Atmospheric emission of reactive nitrogen during biofuel ethanol production - Machado, Cristine M. D. [UNESP]; Cardoso, Arnaldo Alves [UNESP]; Allen, Andrew G. [UNESP] (Amer Chemical Soc, 2008)
This paper evaluates emissions to the atmosphere of biologically available nitrogen compounds in a region characterized by intensive sugar cane biofuel ethanol production. Large emissions of NH(3) and NO,, as well as particulate nitrate and ammonium, occur at the harvest when the crop is burned, with the amount of nitrogen released equivalent to similar to 35% of annual fertilizer-N application. Nitrogen oxides concentrations show a positive association with fire frequency, indicating that biomass burning is a major emission source, with mean concentrations of NO, doubling in the dry season relative to the wet season. During the dry season biomass burning is a source of NH3, with other sources (wastes, soil, biogenic) predominant during the wet season. Estimated NO(2)-N, NH(3)-N, NO(3)(-)-N and NH(4)(+)-N emission fluxes from sugar cane burning in a planted area,of ca. 2.2 x 10(6) ha are 11.0, 1.1, 0.2, and 1.2 Gg N yr(-1), respectively.